PENDEKATAN HERMENEUTIKA UNTUK GERAKAN GENDER - Ismatul Izzah (Al-Fikru : Jurnal Pendidikan Dan Sains, 2021)
Gender is a reality called men and women and the division of social roles. Tinnjaun related to gender issues places women outside their nature and often returns to the position of women being subordinated again or vice versa. Investigating the hermeneutics of Amina Wadud's interpretation of Al-Qur'an verses related to gender issues is the aim of this research. Critical method The analysis was carried out to explore Amina Wadud's ideas and the data taken from references from various correct sources. She emphasized her thoughts on gender issues from personal, family, intellectual, and cultural backgrounds. Furthermore, there were no truly neutral translators. There is no truly neutral interpreter which implies the statement he conveys. He recommends a descriptive critical analysis method with a hermeneutic approach to reduce tendensisus and interpreter selfishness in interpreting texts, especially gender issues. Hermeneutics stands on the study of language, history, and contextualization. Fazlur Rahman is a figure who influences Wadud's hermeneutic interpretation. Keyword: Gender; Hermeneutika; Amina Wadud;